Influence of aggregate mineralogical composition on water resistance of aggregate–bitumen adhesion - Zhang, Jizhe; Apeagyei, Alex K.; Airey, Gordon D.; Grenfell, James R.A. (Elsevier, 2015)
The effects of aggregate mineralogical composition on moistures sensitivity of aggregate–bitumen bonds were investigated using four aggregate types (two limestone and two granite)and two bitumen grades (40/60 penand70/100pen). Moisture sensitivity (or water resistance) of the aggregate–bitumen bonds were characterized using retained strength obtained from three different tensile tests (peel, PATTI and pull-off). The results showed significant differences in the amount of moisture absorbed by a given aggregate which suggested strong correlations between aggregate mineral composition and moisture absorption. For most of the aggregate–bitumen bonds, failure surfaces transformed from cohesive to adhesive with conditioning time there by confirming the strong influence of moisture on aggregate bonds. The three tensile tests used in this study showed similar rankings in terms of moisture sensitivity but the pull-off test was found to be the most sensitive. The effect of bitumen on moisture sensitivity was found to be lower than the effect of aggregates, with the moisture absorption properties of the aggregates depending strongly on certain key minerals including clay, anorthite and calcite. Strong correlations ere also found between mineral compositions and moisture sensitivity with clay and anorthite having strong negative influence while calcite showed positive effect on moisture sensitivity. Previous studies have identified various mineral phases like albite, quartz, and k-feldspar, as detrimental in terms of moisture sensitivity.The results appear to support the extension of the existing list of detrimental aggregate minerals to include anorthite and clay while supporting the case of calcite as a moisture resistant mineral.